Bacterial communities at a groundwater‐surface water ecotone: gradual change or abrupt transition points along a contamination gradient?. (11th August 2021) - Lehosmaa, Kaisa; Muotka, Timo; Pirttilä, Anna Maria; Jaakola, Iikka; Rossi, Pekka M.; Jyväsjärvi, Jussi
Summary: Microbial communities contribute greatly to groundwater quality, but the impacts of land‐use practices on bacteria in groundwaters and groundwater‐dependent ecosystems remain poorly known. With 16S rRNA gene amplicon sequencing, we assessed bacterial community composition at the groundwater‐surface water ecotone of boreal springs impacted by urbanization and agriculture, using spring water nitrate‐N as a surrogate of contamination. We also measured the rate of a key ecosystem process, organic matter decomposition. We documented a recurrent pattern across all major bacterial phyla where diversity started to decrease at unexpectedly low nitrate‐N concentrations (100–300 μg L −1 ). At 400 NO3 − ‐N μg L −1, 25 bacterial exact sequence variants showed a negative response, resulting in a distinct threshold in bacterial community composition. Chthonomonas, Acetobacterales and Hyphomicrobium were the most sensitive taxa, while only three taxa ( Duganella, Undibacterium and Thermoanaerobaculaceae ) were enriched due to increased contamination. Decomposition rate responded unimodally to increasing nitrate‐N concentration, with a peak rate at ~400 NO3 − ‐N μg L −1, parallelly with a major shift in bacterial community composition. Our results emphasize the utility of bacterial communities in the assessment of groundwater‐dependent ecosystems. They also call for a careful reconsideration of threshold nitrate values for defining groundwater ecosystem health and protecting their microbial biodiversity.